Left Ventricular Diastolic Dysfunction in Patients of Type-II Diabetes Mellitus: A Cross Sectional Study (Medical Forum Monthly, 2024)
Objective: To determine the frequency of left ventricular diastolic dysfunction in patients with type II diabetes mellitus. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Department of Medicine, KTH Peshawar for six months from February to July 2018. Materials and Methods: A total of 171 type-II diabetic patients were observed. After informed written consent, inclusion and exclusion criteria, all patients were subjected to detailed history, clinical examination and measurement of Body Mass Index in term of kg/m2 using standard weight machine and measuring tape. Following this, they were subjected to standard M Mode echocardiography to measure Left Ventricular Diastolic Function. Results: Total 171 (100%) patient, 72(42%) male and 99(58%) females with a mean age of 52±7.25 years, mean duration of type-II DM 14±4.372 years, mean BMI 27±3.11 were enrolled in the study. Total 72(42%) patients were diagnosed with LVDD. It was more prevalent among female 41 (24%) than males 31(18.1). None of P-value showed significant result. Conclusion: Study concludes that the frequency of left ventricular diastolic dysfunction is quite high in female type-II diabetes mellitus. Longer the duration of Diabetes and greater the BMI, more prevalent LVDD is in Type-II DM.